Penerapan Tungku Pengasapan Tebiyama Pada Pembuatan Ikan Kayu - Frets Jonas Rieuwpassa; Aprelia M. Tomasoa; Wendy A. Tanod; Edward Irsan L. Ferre; Marnens Ch. Karaeng (Jurnal FishtecH, 2022)
The tebiyama is an alternative for producing wooden fish in the islands such as ’Nusa Utara’ which is abundant in the production of small pelagic fish, especially Decapterus sp. and Euthynnus affinis. The purpose of this study was to see the chemical quality of wooden fish produced using by tebiyama. The stages consist of the preparation stages including weighing, cutting, washing, boiling, removing the bones, drying 1 and drying 2. Furthermore, the fish is smoked using a tebiyama for 30 hours at 60-65oC, every 10 hours the fish is rested for 24 hours. The wooden fish was calculated yield and proximate. The yield results were obtained for Decapterus sp. by 35,9% and Euthynnus affinis by 42,9%. The proximate (moisture, protein, fat and ash) showed that the wooden fish from Decapterus sp. had a moisture content of 16.16%, a fat content of 7.81%, a protein content of 70.02% and an ash content of 2.31% while the wooden fish from Euthynnus affinis had a moisture content of 16.06. %, fat content 10.12%, protein content 70.72% and ash content 2.5%. The moisture content of wooden fish produced with the tebiyama meets SNI 2691.1-2009.